2021
DOI: 10.1136/bmjdrc-2020-001975
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and liver histopathology in metabolically unhealthy subjects do not correlate with the hepatic abundance of NLRP3 inflammasome nor circulating IL-1β levels

Abstract: IntroductionSystemic chronic low-grade inflammation has been linked to insulin resistance (IR) and non-alcoholic steatohepatitis (NASH). NOD-like receptor protein 3 (NLRP3) inflammasome and its final product, interleukin (IL)-1β, exert detrimental effects on insulin sensitivity and promote liver inflammation in murine models. Evidence linking hepatic NLRP3 inflammasome, systemic IR and NASH has been scarcely explored in humans. Herein, we correlated the hepatic abundance of NLRP3 inflammasome components and IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…Consistent with these findings, our study found tight correlations between the protein expressions of NLRP3 inflammasome components and insulin resistance, and liver pathology in elderly pre-diabetic subjects. However, a recent study found that insulin resistance and liver histopathology in metabolically unhealthy subjects did not correlate with the hepatic abundance of NLRP3 inflammasome nor circulating IL-1β levels ( 44 ). The most likely reason for the discrepancy may that the objects in this study were less obese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these findings, our study found tight correlations between the protein expressions of NLRP3 inflammasome components and insulin resistance, and liver pathology in elderly pre-diabetic subjects. However, a recent study found that insulin resistance and liver histopathology in metabolically unhealthy subjects did not correlate with the hepatic abundance of NLRP3 inflammasome nor circulating IL-1β levels ( 44 ). The most likely reason for the discrepancy may that the objects in this study were less obese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…NLRP3 activation up-regulates fibrotic markers in hepatic stellate cells and Nlrp3 knock-in mice demonstrate increased liver fibrosis and enhanced collagen production, even independent of the degree of inflammation [67]. However, studies demonstrating a key role of NLRP3 in human MASLD are still rare, and there is a clear need for further studies [68]. This is important as NLRP3 can be antagonized by various drugs such as MCC950, which specifically neutralizes NLRP3 and has been shown to improve MASH pathology, including inflammation and liver fibrosis [69].…”
Section: Inflammasomes: Key Factors In Masldmentioning
confidence: 99%